Reentrance phenomenon in superconductor/ferromagnet nanostructures and their application in superconducting spin valves for superconducting electronics - Sidorenko, A.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
In superconductor/ferromagnet layered structures, a Fulde–Ferrell–Larkin–Ovchinnikov-like inhomogeneous superconducting pairing give rise. The singlet and zero-projection triplet components of the pairing oscillate in space, and the presence of interfaces causes interference phenomena. As the result of the interference, the superconducting critical temperature Tc oscillates as a function of the ferromagnetic layer thicknesses or, even more spectacular, reentrant superconductivity appears. Two ferromagnetic layers can be combined with a superconducting layer into a superconducting spin valve. Proper design and choice of the material parameters give possibility to control superconducting Tc manipulating with magnetic configurations in the system. The conditions to get large spin-valve effect, i.e., a large shift in the critical temperature, are reviewed in the article.